Unity or Divergence: Nahdlatul Ulama and Muhammadiyah Perspective on Interfaith Moderation - Aulia, Sulthonul; Maulana Fajrin, Ardhi; Ceesay, Abdoulie; Birkbeck, Musa Jallow (Pusat Kajian Moderasi Beragama dan Ideologi Pancasila UIN Sulthan Thaha Saifuddin Jambi, 2024)
This study delves into the perspectives of Nahdlatul Ulama and Muhammadiyah members on the value of interfaith moderation in Indonesia. As the two foremost Islamic organizations, both play pivotal roles in shaping religious discourse and fostering harmony among diverse religious communities. Despite both organizations claiming adherence to Moderate Islam, this research identifies potential gaps between the conceptualization and grassroots implementation of these values. Differing interpretations arise, mainly due to the lack of a precise definition of